Potensi Sengketa Hak Atas Tanah di Indonesia - Permadi, Iwan Permadi (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The failure to overcome various land issues in Indonesia is a big homework for the government, because there are internal factors from unscrupulous state officials who contribute to land crimes apart from negligence and lack of prudence of the community. This research examines the potential land problems and factors that cause the recurrence of land conflicts in Indonesia. The research method used is normative juridical with statutory approach and conceptual approach. The results of the research show that the recurrence of conflicts over land is due to weak legal protection of community lands, weak law enforcement and the existence of partisanship being the cause of unsolved land conflicts in Indonesia which makes legal issues regarding land do not lead to the objectives of legal certainty and justice. Keywords : Potential; Dispute; Land